Bench-to-bedside review: Hypercapnic acidosis in lung injury - from 'permissive' to 'therapeutic' - Marloes M. IJland; Leo Heunks; Johannes G. van der Hoeven (2010)
Modern ventilation strategies for patients with acute lung injury and acute respiratory distress syndrome frequently result in hypercapnic acidosis (HCA), which is regarded as an acceptable side effect ('permissive hypercapnia'). Multiple experimental studies have demonstrated advantageous effects of HCA in several lung injury models. To date, however, human trials studying the effect of carbon dioxide per se on outcome in patients with lung injury have not been performed. While significant concerns regarding HCA remain, in particular the possible unfavorable effects on bacterial killing and the inhibition of pulmonary epithelial wound repair, the potential for HCA in attenuating lung injury is promising. The underlying mechanisms by which HCA exerts its protective effects are complex, but dampening of the inflammatory response seems to play a pivotal role. After briefly summarizing the physiological effects of HCA, a critical analysis of the available evidence on the potential beneficial effects of therapeutic HCA from in vitro, ex vivo and in vivo lung injury models and from human studies will be reviewed. In addition, the potential concerns in the clinical setting will be outlined.